Pelatihan Digitalisasi Usaha Kopi Berbasis Techno Entrepreneurship di Desa Huta Tinggi, Kabupaten Samosir - Marpaung, Astrida N; Khairunnisa, Khairunnisa; Rahmi, Elvika; Hulu, Delisman; Lumbanbatu, Maristella J.; Silitonga, Keyzia Tripema S.; Lumban Tobing, Yusuf Andre Steven (CV. Devi Tara Innovations, 2026)
Huta Tinggi Village, Samosir Regency, has local coffee potential that has not been optimally managed, particularly in digital marketing and branding aspects. This Community Service Program aimed to digitalize the coffee business based on techno-entrepreneurship to enhance the competitiveness and sustainability of local MSMEs. The methods included digital marketing training, creation of marketplace and social media business accounts, development of a digital product catalog, strengthening of branding and packaging design, and digital promotion assistance. The results showed a 48% increase in partners’ digital literacy, activation of digital business accounts, and a 30% increase in sales after implementing digital marketing strategies. The program proved effective in expanding market reach, improving partners’ capacity, and strengthening the competitiveness of Huta Tinggi coffee products.